Temperature dependence of blood surface tension - Rosina, Jozef; Kvašňák, Eugen; Šuta, Daniel; Kolářová, Hana; Málek, Jiří; Krajči, Ladislav (Physiological research, 2007)
Whole blood surface tension of 15 healthy subjects recorded by the ring method was investigated in the temperature range from 20 to 40 degrees C. The surface tension omega as a function of temperature t ( degrees C) is described by an equation of linear regression as omega(t) = (-0.473 t + 70.105) x 10(-3) N/m. Blood serum surface tension in the range from 20 to 40 degrees C is described by linear regression equation omega(t) = (-0.368 t + 66.072) x 10(-3) N/m and linear regression function of blood sediment surface tension is omega(t) = (-0.423 t + 67.223) x10(-3) N/m.
Keywords: Temperature; krev - fyziologické jevy; Linear Models; Reference Values; lineární modely; biologické modely; povrchové napětí; Models, Biological; lidé; Humans; teplota; Surface Tension; referenční hodnoty; Blood Physiological Phenomena